Implementación de un algoritmo genético para la asignación de aulas en un centro de estudio (ING) - Solano Sabatier, Yadira (2008)
The genetic algorithm is a very efficient tool to solve optimization problems. On the other hand, the classroom assignation in any education center, particularly those that does not have enough quantity of classrooms for the courseʼs demand converts it in an optimization problem. In the Department of Computer Science (Universidad de Costa Rica) this work is carried out manually every six months. Besides, at least two persons of the department are dedicated full time to this labor for one week or more. The present article describes an automatic solution that not only reduces the response time to seconds but it also finds an optimal solution in the majority of the cases. In addition gives flexibility in using the program when the information involved with classroom assignation has to be updated. The interface is simple an easy to use.